SPE Western Regional Meeting 1999
DOI: 10.2118/54630-ms
|View full text |Cite
|
Sign up to set email alerts
|

Non-Darcy and Multiphase Flow in Propped Fractures: Case Studies Illustrate the Dramatic Effect on Well Productivity

Abstract: This paper was prepared for presentation at the 1999 SPE Western Regional Meeting held in Anchorage, Alaska, 26–28 May 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 20 publications
0
37
0
1
Order By: Relevance
“…Multiphase and non-Darcy flow effects in hydraulically fractured gas reservoirs also reduce fracture productivity in the field (Vincent et al, 1999;Schubarth et al, 1995). Flowers et al (2003) found that gas reserves for each well could be increased with increased fracture conductivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Multiphase and non-Darcy flow effects in hydraulically fractured gas reservoirs also reduce fracture productivity in the field (Vincent et al, 1999;Schubarth et al, 1995). Flowers et al (2003) found that gas reserves for each well could be increased with increased fracture conductivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At higher Reynolds numbers, the velocity and hydraulic gradient do not exhibit a linear relationship. Therefore, use of Darcy's law can cause considerable error in the post-laminar conditions such as the calculation of well productivity [3] and the discharge measurement and design of pumping wells, hydraulic structures such as rock fill dams [4,5], water treatment filters and fissured rocks. Therefore, the characterization and modeling of flow through porous media is pertinent since the issue aptly addresses the abovementioned challenges.…”
Section: Introductionmentioning
confidence: 99%
“…There is more evidence that the non-Darcy flow at high flow rates occurs in many subsurface, engineering porous and biological porous flow systems (Schfer and Lohnert, 2006;Vafai, 2010;Wu et al, 2011). Motivated by its importance in practical applications and scientific interest, understandings about the flow behavior at high flow rates have been developed by means of experimental and numerical analysis (Evans et al, 1987;Huang and Ayoub, 2008;Mayaud et al, 2014;Pereira et al, 2006;Vincent et al, 2000;Ye et al, 2014). The Forchheimer equation has been used extensively to describe such high velocity flow (Ergun, 1952;Forchheimer, 1901;Wu, 2001;Wu, 2002), which adds a quadratic flow term to account for high velocity inertial effects.…”
Section: Introductionmentioning
confidence: 99%